Metode Zmijewski untuk Memprediksi Financial Distress pada Perusahaan Consumer Non-Cyclicals di Indonesia - Setiawan, Nabiil Afifah Putri; Sari, Shinta Permata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Financial distress is a stage of decline in financial conditions that occurs before bankruptcy or liquidation. This study aims to analyze the influence of Total Asset Turnover, Interest Coverage Ratio, Earning per Share, and Net profit Margin on Financial Distress. The population of this study comprises all companies listed on the Indonesia Stock Exchange from 2021 to 2023. The sampling technique used is purposive sampling method, resulting in a sample of 75 non-cyclical consumer companies on the Indonesia Stock Exchange that met the criteria. Financial distress is measured using the Zmijewski model. The research method employed is quantitative research. The data source of this study is secondary data in the form of the company's annual financial report. The data analysis technique is binary logistic regression analysis using SPSS 26 software. The results of the study indicate that the Total Asset Turnover and Earning per Share have influence on financial distress, while the Interest Coverage Ratio and Net Profit Margin has no influence on financial distress.